Effect of plant growth regulators on micropropagation of saba banana (Musa Balbisiana Cv. Saba) - Lee Mei Li, Aubrey Mei Li (Universiti Malaysia Sabah, 2017)
A laboratory based experiment was conducted in Plant Tissue Culture laboratory at Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, Sandakan Campus to study the effect of plant growth regulators on micropropagation of Saba banana (Musa ba!bisiana cv. Saba). The objective of this study was to determine the effect of different concentrations of plant growth regulators on micropropagation of Saba banana. The experimental design used was Completely Randomized Design using Murashige and skoog media, there were seven treatments which were MS O (control), MS media supplemented with different types and concentrations of plant growth regulators which were 2.5 mg/L BAP, 5.0 mg/L BAP, 7.5 mg/L BAP, 2.5 mg/L BAP with 0.5 mg/L NAA, 5.0 mg/L BAP with 0.5 mg/L NAA, 7.5 mg/L BAP with 0.5 mg/L NAA respectively, each treatment had seven replicates. Data were recorded twice a week for four months. Results were analysed using Statistical Analysis System (SAS) version 9.4. All the collected data were analyzed using the One Way Analysis of Variance (ANOVA) with the significant level at 0.05. Least Significant Difference was used to determine the significant difference between the treatments in this study. Results obtained from this study showed that MS media supplemented with 5.0 mg/L performed better than other treatments, however the growth response of Saba banana is rather slow, phenolization of explant caused necrosis on explant.